2012
DOI: 10.4269/ajtmh.2012.12-0306
|View full text |Cite
|
Sign up to set email alerts
|

Scrub Typhus: Surveillance, Clinical Profile and Diagnostic Issues in Shandong, China

Abstract: Abstract. To elucidate the epidemic status, clinical profile, and current diagnostic issues of scrub typhus in Shandong Province, we analyzed the surveillance data of scrub typhus from 2006 to 2011 and conducted a hospital-based disease survey in 2010. Scrub typhus was clustered in mountainous and coastal areas in Shandong Province, with an epidemic period from September to November. The most common manifestations were fever (100%), eschar or skin ulcer (86.3%), fatigue (71.6%), anorexia (71.6%), and rash (68.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 31 publications
11
43
0
Order By: Relevance
“…12 A necrotic eschar which is considered as most useful diagnostic clue for scrub typhus was present in 46(45%) cases of our study population similar to a study done in Taiwan though it was reported as high as 86.3% in some study and also as low as 5%. [13][14][15] In our present study the commonest site of eschar was inguinal region 18%, followed by trunk and axilla, similar to the study by Jamil. 16 Few patients had eschar in the inframammary region and one had penile eschar.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…12 A necrotic eschar which is considered as most useful diagnostic clue for scrub typhus was present in 46(45%) cases of our study population similar to a study done in Taiwan though it was reported as high as 86.3% in some study and also as low as 5%. [13][14][15] In our present study the commonest site of eschar was inguinal region 18%, followed by trunk and axilla, similar to the study by Jamil. 16 Few patients had eschar in the inframammary region and one had penile eschar.…”
Section: Discussionsupporting
confidence: 77%
“…The rash present was mostly maculo-papular type, present in about 33% of cases. The lymphadenopathy were mostly painful with decreasing order of distribution inguinal (14), cervical (8), axillary (2). Eschar was most commonly found in the inguinal region.…”
Section: Geographic Distribution Of Scrub Typhusmentioning
confidence: 99%
“…15,16 Lymphadenopathy usually painful, is a common finding in scrub typhus reported in 13 to 18% of patients. [17][18][19] In this study, all patients had fever followed by anorexia, headache, jaundice and lymphadenopathy. Eschar formation was seen only in 8% of the patients.…”
Section: 11mentioning
confidence: 99%
“…[40][41][42] Unresolved clinical issues include the reason for the wide range of occurrence of eschars (7-97%), the reason for rash and severity of illness, and the need for characterization and determination of the mechanisms of the coagulopathy, hemorrhages, interstitial pneumonia, and meningoencephalitis. [43][44][45] There is currently no unified approach to assess and stratify 33,46,47 Strain virulence in experimental animals does not correlate sufficiently with strain virulence for humans to be used as a yardstick of pathogenicity. 48,49 An important unresolved issue is the identification of bacterial virulence mechanisms and host-determined mechanisms that affect disease severity ( Table 2).…”
mentioning
confidence: 99%